2012
DOI: 10.1007/s00586-012-2447-0
|View full text |Cite
|
Sign up to set email alerts
|

Three- and four-level anterior cervical discectomy and fusion with a PEEK cage and plate construct

Abstract: Introduction Three-or four-level anterior cervical discectomy and fusion with autograft and plate fixation have demonstrated relatively good fusion rates and outcomes, but donor site morbidity and the limitations of autograft harvest remain problematic. The purpose of this study is to assess the radiographic and clinical outcomes of three-or four-level anterior cervical discectomy and fusion with a PEEK cage and plate construct. Methods This retrospective review included 43 consecutive patients who underwent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 33 publications
(64 reference statements)
1
31
1
3
Order By: Relevance
“…To increase fusion rates, prevent subsidence and restore cervical sagittal alignment, additional anterior cervical plating has been recommended for cage fixation [29]. However, rigid anterior cervical plate fixation may shield the mechanical load that is very important for fusion.…”
Section: Discussionmentioning
confidence: 99%
“…To increase fusion rates, prevent subsidence and restore cervical sagittal alignment, additional anterior cervical plating has been recommended for cage fixation [29]. However, rigid anterior cervical plate fixation may shield the mechanical load that is very important for fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Перелом тела С 7 позвонка наблюдали в 2 (6,6 %) случа-ях, миграцию каудального терминаль-ного отдела аутотрансплантата кпере-ди -в 2 (6,6 %), выкручивание винтов -в 2 (6,6 %), несращение -в 4 (13,3 %). В своем исследовании Song et al [40] анализировали результаты при-менения гибридных ротационных динамических пластин «Maxima», «U&I Corporation», совместно с кейд-жами РЕЕК, «Stryker», при выполне-нии мультисегментарного переднего межтелового спондилодеза у 43 боль-ных с заболеваниями ШОП. Среди осложнений авторы отмечали тран-зиторную дисфагию у 4 (9,3 %) боль-ных, 3 (3,9 %) пациента испытывали затруднения при дыхании на протя-жении нескольких дней после опера-ции, охриплость -у 1 (2,3 %) больного.…”
Section: осложнения при применении гибрид-ных динамических пластинunclassified
“…Для стабилизации тел шейных позвонков при выполнении перед-него межтелового спондилодеза в последнее время все чаще исполь-зуют динамические пластины [34,37,40,44]. Информация о положи-тельных результатах их примене-ния в хирургическом лечении забо-леваний и повреждений шейного отдела позвоночника (ШОП) начала появляться в специализированных источниках с 1998 г.…”
unclassified
“…Reducing the need for circumferential procedures is a significant advantage of ACDF over ACCF as these procedures have a high degree of associated morbidity. Several series report complication rates in the range of 31 to 56% for 3 level corpectomies with posterior instrumentation [8,68,62].…”
Section: Surgical Options For Multilevel Disease: Acdf Vs Accfmentioning
confidence: 99%
“…Prior to recent advances in anterior plating systems and grafting materials, multilevel ACDF was associated with a significantly higher non-union rate than ACCF, especially when treating multilevel disease [16,43,30]. Historically, fusion rates following non-instrumented multilevel ACDF (3 level or greater) were unacceptably low [34,62,71]. Early studies suggested that corpectomy without instrumentation was associated with much higher fusion rate than multilevel interbody grafting without instrumentation [68,11].…”
Section: Surgical Options For Multilevel Disease: Acdf Vs Accfmentioning
confidence: 99%